Global Warming Deniers. (5th November 2014) - McNulty, Geoff
Abstract : Over recent years, I have engaged with mountains of media information dealing with the general subject of Global Warming and Climate Change and overall, the argument 'for' has been very convincing. So I pause at this point and own up to holding the view that the earth is indeed warming at an (alarmingly) accelerated pace, however I acknowledge this is by no means a universally shared perspective.